Counsellor Communication Style as a Determinant of Rater-Perceived Empathy - Rennie, David L.; Burke, Harley L.; Toukmanian, Shaké G. (Canadian Journal of Counselling and Psychotherapy, 2012)
Carkhuff-scale empathy of 64 counsellors was judged by two randomly sampled raters from each of two sources of raters. Each counsellor was evaluated both with his client present in the transaction (unedited tape material) and with his client's utterances erased (edited material). In a second phase of the study, the average empathy scores of the four raters were regressed against three linguistic and three paralinguistic attributes of counsellor communication. Separate regressions were conducted for the empathy ratings given to the unedited versus edited material. The results of the first part of the study paralleled earlier findings of Truax indicating that when empathy ratings on the unedited material were correlated with the ratings in the edited material, the result approximated the interrater reliability of the scale. The results of the two multiple regressions were similar and supported the hypothesis that, in rating unedited material, empathy raters focus more on the style of the counsellor's response than on the relationship between the response and the client utterance preceding it. The validity of this deductive method of discriminating is discussed.